Espindolol for the treatment and prevention of cachexia in patients with stage III/IV non‐small cell lung cancer or colorectal cancer: a randomized, double‐blind, placebo‐controlled, international multicentre phase II study (the ACT‐ONE trial). Issue 3 (1st July 2016) - Stewart Coats, Andrew J.; Ho, Gwo Fuang; Prabhash, Kumar; von Haehling, Stephan; Tilson, Julia; Brown, Richard; Beadle, John; Anker, Stefan D.
Abstract: Background: Cancer cachexia is a major cause of morbidity and mortality with no widely approved treatment. Methods: The ACT‐ONE trial is a randomized, double‐blind, parallel group, placebo‐controlled, phase II multicentre trial in patients (25‐80 years) with stages III or IV colorectal cancer or non‐small cell lung cancer‐related cachexia that tested two doses of espindolol (a novel non‐selective β blocker with central 5‐HT1a and partial β2 receptor agonist effects). The primary endpoint was the difference in the rate of weight change over 16 weeks (linear mixed‐effect model for repeated measures) between high‐dose espindolol and placebo. Results: Eighty‐seven patients were randomized centrally in blocks in a ratio 3:2:1 [42 high dose, 10 mg twice daily (bd):31 placebo:14 low dose, 2.5 mg bd]. High‐dose espindolol produced a statistically and clinically significant weight gain (+0.54 kg/4 weeks, 95% CI 0.38–0.70) compared with a weight loss on placebo (−0.21 kg/4 weeks, 95% CI ‐0.37–0.05); P < 0.0001. High‐dose espindolol produced a statistically significant increase in lean body mass, whilst changes in fat mass were neutral. Hand grip strength significantly (high dose −1.15 ± 0.7 kg, placebo −3.51 ± 0.8 kg change per 4 weeks; P = 0.0134), stair climbing power, and 6‐min walk test non‐significantly were all directionally in favour of high‐dose espindolol. There were no clinically significant differences in safety signals or survival between treatment groups, although a numerical excess of dyspnoea was seen with high‐dose espindolol (19.1%) compared with placebo (3.2%). Conclusions: This positive trial showed that espindolol 10 mg bd significantly reversed weight loss, improved fat free mass, and maintained fat mass in advanced colorectal cancer and non‐small cell lung cancer‐related cachexia. This was associated with a significant improvement in handgrip strength, supporting the further investigation of 10 mg bd espindolol for the treatment of cancer cachexia. Although not powered to look at dose response, most treatment effects for low dose lay between high dose and placebo, suggesting that there may be a dose response in the effects of espindolol.